After 2 change of variables, and a $x = \log(u)$ transformation, I have this integral...

$$\int_0^{\infty } \frac{\alpha e^x}{\lambda-e^x \lambda+e^{\alpha x}} \, dx$$

What are some recommendations on how to integrate this?

NOTE: The original integral looked like:

$$\int_{1 }^{\infty } \frac{\alpha \left(\frac{1 }{x}\right)^{\alpha }}{1-\lambda (x-1 ) \left(\frac{1 }{x}\right)^{\alpha }} \, dx$$

and for the integral to converge $\alpha > 1$.

Finally, when $\alpha = 2$, I did get this expression...

$$\frac{8 \tan ^{-1}\left(\frac{\sqrt{\lambda }}{\sqrt{4-\lambda }}\right)}{\sqrt{(4-\lambda ) \lambda }}$$


  • 2
    $\begingroup$ The substitution $u:=e^x$ turns the integral into $$\int_1^\infty\frac{\alpha}{\lambda-\lambda u + u^\alpha}du$$ which is still pretty bad but maybe more tractable. Do you know anything about $\alpha$? $\endgroup$ – Tom Feb 25 '17 at 13:16
  • $\begingroup$ Yes - for the integral to converge, $\alpha > 1$ $\endgroup$ – PiE Feb 25 '17 at 13:17
  • $\begingroup$ @Tom - I tried that substitution, but didn't make much progress...but then again...Next, I transformed it into the one on top... $\endgroup$ – PiE Feb 25 '17 at 13:20
  • $\begingroup$ to get a nice closed form you should at least have the transoformed numerator to be a polynomial in $x$ $\endgroup$ – tired Feb 25 '17 at 13:52

For integer $\alpha>1$, I got the following:

Take the Mellin transform of the integrand with respect to $\lambda$, $$ \int_0^\infty \frac{\alpha e^x}{\lambda-e^x \lambda+e^{\alpha x}} \lambda^{s-1} \; d\lambda = \frac{\alpha e^{x-\alpha x}}{(-e^{-\alpha x}(e^x-1))^s}\pi\csc(\pi s) = I_{\alpha}(s,x) $$ now integrate over $x$ $$ \int_0^\infty I_{\alpha}(s,x) \; dx = (-1)^{-s}a\pi\csc(\pi s)\frac{\Gamma(1-s)\Gamma(\alpha-1+s-\alpha s)}{\Gamma(\alpha-\alpha s)} $$ now take the inverse Mellin transform with respect to $s$ to get something that depends on $\alpha$ and $\lambda$, $$ G_\alpha(\lambda) = \frac{1}{2 \pi i}\int_{c-i \infty}^{c + i \infty} \lambda^{-s}(-1)^{-s}a\pi\csc(\pi s)\frac{\Gamma(1-s)\Gamma(\alpha-1+s-\alpha s)}{\Gamma(\alpha-\alpha s)}\;ds $$ we can use the Mathematica command

InverseMellinTransform[((-1)^-s a [Pi] Csc[[Pi] s] Gamma[ 1 - s] Gamma[-1 + a + s - a s])/Gamma[a - a s] /. a -> 2, s, l]

Where the a -> X part can be changed for various values of $\alpha$. This reproduces your result for $\alpha=2$, but that obscures the hypergeometric nature of the result. It also gives results for higher values of $\alpha$ as hypergeometric functions weighted by products of gamma functions.

The results seem to have a pattern $$ G_4(\lambda)=\frac{3^2}{2^3}\sqrt{\frac{3}{2}}\frac{\Gamma(\frac{4}{3})\Gamma(\frac{5}{3})}{\Gamma(\frac{5}{4})\Gamma(\frac{7}{4})}\;_4F_3\left(\frac{3}{3},\frac{3}{3},\frac{4}{3},\frac{5}{3}\bigg|\frac{5}{4},\frac{6}{4},\frac{7}{4}\bigg|\frac{3^3}{4^4}\lambda\right) $$ $$ G_5(\lambda)=\pi\frac{4^3}{5^3}\sqrt{\frac{2}{5}}\frac{\Gamma(\frac{5}{4})\Gamma(\frac{7}{4})}{\Gamma(\frac{6}{5})\Gamma(\frac{7}{5})\Gamma(\frac{8}{5})\Gamma(\frac{9}{5})}\;_5F_4\left(\frac{4}{4},\frac{4}{4},\frac{5}{4},\frac{6}{4},\frac{7}{4}\bigg|\frac{6}{5},\frac{7}{5},\frac{8}{5},\frac{9}{5}\bigg|\frac{4^4}{5^5}\lambda\right) $$ In general it appears that $$ G_n=C_n\; _nF_{n-1}\left(\frac{n-1}{n-1},\frac{n-1}{n-1},\frac{n}{n-1},\cdots,\frac{2n-3}{n-1}\bigg|\frac{n+1}{n},\frac{n+2}{n},\cdots,\frac{2n-1}{n}\bigg|\frac{(n-1)^{n-1}\lambda}{n^n}\right) $$ where $$ C_n=\sqrt{\frac{2\pi(n-1)}{n}}\frac{(n-1)^{n-2}}{n^{n-2}}\frac{\prod_{k=0}^{n-2} \Gamma(\frac{n+k}{n-1})}{\prod_{k=1}^{n-1} \Gamma(\frac{n+k}{n})} $$ where we see your result in $C_2=2$ and $$ _2F_1\left(1,1\bigg|\frac{3}{2}\bigg|\frac{\lambda}{4}\right) = \frac{4 \sin^{-1}(\sqrt{\lambda}/2)}{\sqrt{(4-\lambda)\lambda}} $$ seems to check out for a few numerical examples.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.